Identification of the novel HLA‐A*11:192 allele by HLA typing of a Caucasian individual. Issue 5 (2nd October 2014) - Todorova, K.; Zuber, K.; Neuwirt, P.; Arnold, R.; Schönemann, C.; Schulze, H.
Abstract We report the new HLA‐A*11:192 allele differing from A*11:01 by one nucleotide in exon 2.